On the Socio-Cultural Determinants of Polish Entrepreneurs’ Attitudes towards the Development of Renewable Energy: Business, Climate Skepticism Ideology and Climate Change - Piotr Żuk (Energies, 2021)
This article analyses the business community in Poland and their views on climate change and the objectives of the European Green Deal (EGD). The authors focus on the analysis of the attitude of entrepreneurs towards the cultural and ideological stereotypes promoted by climate denialists. This article shows that the ideological factor may play a certain role in shaping the attitudes of entrepreneurs towards energy transition. The research was carried out on a sample of 400 entrepreneurs. The research results indicate that the ideological factor is of particular importance among entrepreneurs who are concerned about the costs of energy transition and the expenditure related to the implementation of the EGD for economic reasons. According to the authors, the stereotypes promoted by climate sceptics may find fertile ground, particularly when accompanied by fears of additional financial costs. Attitudes towards the goals of energy transition among entrepreneurs usually differ depending on the size of the company: representatives of smaller companies, who have greater concerns about their economic position, are more likely to present the views of climate sceptics. Acceptance for the theory of climate sceptics may also be influenced by the industry sector: those who may lose out on energy transition, such as representatives of the mining industry, may share the myths of climate denialists.